O17.2 Women's experiences with primary human papillomavirus (HPV) testing for cervix screening: HPV focal exit survey results. (14th July 2019) - Smith, Laurie; Niekerk, Dirk Van; Krajden, Mel; Gondara, Lovedeep; Cook, Darrel; Lee, Marette; Martin, Ruth; Stuart, Gavin; Peacock, Stuart; Franco, Eduardo; Coldman, Andrew; Ogilvie, Gina
Abstract : Background: Globally, cervical screening is moving from cytology (Pap) to HPV-based testing. Cytology-based screening has occurred for decades; therefore, engaging the screened population is critical to success of this significant paradigm shift. HPV FOCAL, a large clinical trial, compared primary HPV testing every 4 years to liquid-based cytology (LBC) every 2 years. Participants were surveyed to assess experiences surrounding HPV screening. Methods: Women aged 25–65 (n=19, 009) from two urban centres were randomized to control (LBC) or intervention (HPV) arms, and 16, 374 women attended 48 month exit with HPV/LBC co-testing. At trial entry, women were provided information about HPV, cervical cancer, HPV testing and results. Women completing exit screening were invited to complete a survey assessing attitudes to HPV vs. Pap testing, screening intervals, and receipt of HPV results. Results: Of 14, 535 invites sent, 5, 532(38%) responders completed some or all of the survey with 63% reporting that HPV vs. Pap testing was acceptable; and 54% willing to have HPV testing every 4–5 yrs vs. a Pap every 3 yrs. Concerns regarding HPV positive results differed by age. More women > 50 yrs reported it important for them to know who gave them HPV than younger women (25–34 yrs: 68%; 35–49 yrs: 69%; 50+yrs: 76%). More women 25–34 yrs than >35 yrs would feel judged for having HPV (25–34 yrs: 44%; 35–49 yrs: 36%; 50+yrs: 34%). More women > 50 yrs reported being HPV positive would affect the relationship with a sexual partner (25–34 yrs: 36%; 35–49 yrs: 41%; 50+: 45%). Response differences by education will also be presented. Conclusion: In this large HPV screening trial, the majority of women reported that HPV vs. Pap testing was acceptable and over half would be willing to have HPV testing every 4–5 yrs. Women had varied concerns regarding HPV positive results and responses varied by age. These findings illustrate the importance of comprehensive, targeted communication strategies prior to implementation of primary HPV screening. Disclosure: No significant relationships.